Structural and Diffusion MRI Analyses With Histological Observations in Patients With Lissencephaly - Vasung, Lana; Rezayev, Arthur; Yun, Hyuk Jin; Song, Jae W.; van der Kouwe, Andre; Stewart, Natalie; Palani, Arthi; Shiohama, Tadashi; Chouinard-Decorte, Francois; Levman, Jacob; Takahashi, Emi (Frontiers in Cell and Developmental Biology, 2019)
The development of cortical convolutions, gyri and sulci, is a complex process that takes place during prenatal development. Lissencephaly, a rare genetic condition characterized by the lack of cortical convolutions, offers a model to look into biological processes that lead to the development of convolutions. Retrospective, qualitative, and quantitative analyses of structural MRI and DTI were performed in patients with lissencephaly (N=10) and age/sex matched controls (N=10). In order to identify microstructural correlates of structural MRI and DTI findings, postmortem brains of patients with lissencephaly (N=4) and age matched controls (N=4) were also examined with histology. Patients with lissencephaly had significantly smaller gyrification index and volumes of hemispheric white and gray matter, compared to the age/sex matched control group. However, there was no significant difference between groups in the subcortical gray matter volumes. Although the majority of patients with lissencephaly had a preserved normal-like appearance of major fissures and primary sulci, the spatial distribution of agyric cortical regions was different in patients with LIS1 and DCX mutations. Lastly, in patients with lissencephaly, spatio-temporal distribution of projection pathways were preserved while short- to medium-range cortico-cortical pathways were absent or fewer in number. Our results indicate that in the patients with lissencephaly cortical system is affected more that the subcortical one.